BARRBODY STUDIES AND CLINICAL APPLICATIONS - Chukwuanukwu, R.C; Chukwuanukwu, T.O.G; Afonne, O.J (Journal of Biomedical Investigation, 2015)
One hundred (100) subjects from among staff and students of Nnamdi Azikiwe University, Nnewi Campus and Nnamdi Azikiwe University Teaching Hospital, Nnewi, were screened for the presence of Barr bodies in buccal smear. 41 males and 59 females (1 a known Tuner Syndrome Patient) were studied. Of these, 26{7 males and 12 females with children, and 1 previously diagnosed Tuner Syndrome} subjects, served as positive and negative controls. The buccal smears were stained with Hematoxylin and Eosin (H&E) stain. Results showed that 57 of the 58 female subjects had Barr bodies. No male subject was found to have Barr bodies. None of the positive subjects had more than one Barr body in a cell. A mean Barr body of 22+5.6% standard deviation was obtained for the female subjects. There were slight variations in the Barr body count. Barr body count of married and single female subjects did not show any significant variation at P<0.05. The only female subject without a Barr body had infertility problems though she had no external features of abnormality.